Penerapan Model Problem Based Learning Dengan Strategi Joyfull Learning Menggunakan Media Animasi Untuk Meningkatkan Kemampuan Berpikir Matematis Siswa Pada Materi Pola Bilangan Di Kelas VIII E SMP Negeri 10 Kupang - Manalor, Natalia Christiani (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2023)
This study aims to describe the application of the problem based learning model with a joyfull learning strategy using animation media to improve students' mathematical thinking skills in number pattern material in class VIIIE SMP Negeri 10 Kupang due to the low ability of students' mathematical thinking in learning which is generally teacher-centered where the teacher is still have not applied real problems as a reference for learning. This type of research is classroom action research (CAR). Data collection techniques in this study included student and teacher observation and tests. The results showed that the percentage of classical completeness was 50% in cycle I and increased to 90% in cycle II. In addition, the results of observations on students also increased based on the observations of observer 1 with a value of 82.35 to 94.11, based on observations of observer 2 with a value of 85.29 to 92.64, and observations of observer 3 with a value of 69.11 to 88.23 . The teacher's observation results also increased, based on the teacher's activity sheet data in learning from cycle I with a value of 80.26 according to observer 1's observation to 88.15 and a value of 73.68 based on observer 2's observations to 90.78. So it can be concluded that the application of the problem based learning model with a joyfull learning strategy using animation media can improve students' mathematical thinking skills in the matter of number patterns.